DETERMINANTS OF CONTRACEPTIVES USE AMONG MARRIED WOMEN IN THE AGE GROUP 15-49 - BOUKHALKHAL, Ali; SADKI, Ali (Journal of Social Sciences)
This article presents an analytical reading of the survey results with multiple indicators on clusters 2019: the case of Algeria.The use of contraceptives among married women is closely associated with a range of factors, whether demographic, social or economic, that affect its usage decision. Therefore, this study endeavours to identify the determinants of contraceptives use among married women in the age group (15-49) based on Multiple Indicator Cluster Survey data 2019, the case of Algeria in order to reveal the magnitude of the impact of socio-demographic and economic determinants on the use of contraceptives as well as to explain that based on the particularity of society. Furthermore, the descriptive analytical method was adopted as well as the technique of analysing ready-made statistical data. The results demonstrated the existence of a different effect between demographic, social, economic determinants and the use of contraceptives among married women aged (15-49 years) in Algeria.